Diclofenac does not reduce the risk of acute pancreatitis in patients with primary sclerosing cholangitis after endoscopic retrograde cholangiography. Issue 4 (May 2020) - Koskensalo, Vilja; Tenca, Andrea; Udd, Marianne; Lindström, Outi; Rainio, Mia; Jokelainen, Kalle; Kylänpää, Leena; Färkkilä, Martti
Background: The European Society of Gastrointestinal Endoscopy recommends rectal indomethacin or diclofenac before endoscopic retrograde cholangiopancreatography (ERCP) to prevent post-ERCP pancreatitis. However, data on the prophylactic effect in patients with primary sclerosing cholangitis (PSC) are lacking. Methods: This was a retrospective case-control study. In 2009–2018, a total of 2000 ERCPs were performed in 931 patients with PSC. Case procedures ( N = 1000 after November 2013) were performed after administration of rectal diclofenac. Control procedures ( N = 1000 before November 2013) were performed with the same indication but without diclofenac. Acute post-ERCP pancreatitis and other ERCP-related adverse events (AEs) were evaluated. Results: Post-ERCP pancreatitis developed in 49 (4.9%) procedures in the diclofenac group and 62 (6.2%) procedures in the control group ( p = 0.241). No difference existed between the groups in terms of the severity of pancreatitis or any other acute AEs. The risk of pancreatitis was elevated in patients with native papilla: 11.4% in the diclofenac group and 8.7% in the control group ( p = 0.294). In adjusted logistic regression, diclofenac did not reduce the risk of pancreatitis (odds ratio (OR) = 1.074, 95% confidence interval 0.708–1.629, p = 0.737). However, in generalised estimation equations with the advanced model, diclofenac seemed to diminish the risk of pancreatitis (OR = 0.503) but not significantly ( p = 0.110). Conclusion: In this large patient cohort in a low-risk unit, diclofenac does not seem to reduce the risk of post-ERCP pancreatitis in patients with PSC. The trend in the pancreatitis rate after ERCP is decreasing. The evaluation of the benefits of diclofenac among PSC patients warrants a randomised controlled study targeted to high-risk patients and procedures.